The power of storytelling as a marketing tool in personal branding - Korzh, Aleksandra Sergueevna (2021)
We live in a world where brands and products are becoming partially human (regarding names, concepts and the message they transmit) and people are mostly seen as brands. The job market itself is saturated to the point that people must find countless ways to differentiate themselves from other millions of competitors. Thus, the main goal of this dissertation is to understand how regular individuals can build their own personal brand by using storytelling as a marketing tool. The power of telling stories and inspiring others through words has been going on for ages now, even before the digital came into our lives and shifted completely the way we see the world and people. Many centuries ago people used to draw on walls to tell about their day, now we take Instagram pictures. In order to fully comprehend this matter, the concepts of personal branding and storytelling were described in detail on this dissertation. As a support to the literature review, 9 interviews were conducted to several people with different profiles and professions. To conclude, the interviews and the literature review allowed to comprehend that storytelling is an important tool when building a personal brand with the following features: authenticity, consistency, charisma, purpose, strong personality, creativity, adaptation, convincing, memorable, distinctive and clear.